Personality Development at University Level as Reflected in Works of Researchers in Lithuania in the Period of 1990–2015 - Meškauskienė, Asta (Pedagogika, 2016)
The present article is focused on the works of researchers in Lithuania in the period of restored independence (1990–2015) that analyse the issues of personality development through university studies alongside the identified key trends of research in the area. The article comprises two parts, with the first part of it devoted to the analysis of works of researchers, who view personality development as the educational mission of university, and the second part discusses the major preconditions for the implementation of the mission of personality development through university studies. The overall tendency, well noticeable in the works of Lithuanian researchers published in the period 1990–2015, speaks for the fact that researchers strongly believe in the significance of the educational mission of university to educate the intellectually rich personality capable of thinking critically. The researchers tend to emphasize the important role that liberal thinking plays in the university studies. The researchers consider liberal education of personality to be the exceptionally significant characteristics of higher education, capable of preconditioning the overall education of the type of personality that can have a significant impact on the intellectual and cultural development of the society at large. In the researchers opinion, the essential indicators of university education comprise the individual’s world outlook, well-balanced attitudes towards societal problems and manifestations of diversity among individuals alongside fundamental understanding of processes and solid knowledge in the subject area. University studies in the works of Lithuanian researchers are viewed not as a mere package of services provided for the client but rather as a powerful developmental process of transforming nature. The researchers point out the importance of solid theoretical preparation in the field of broadly understood humanities that is crucial in making university studies significantly meaningful. The value of the acquired skills of critical thinking, in turn, consists in their emancipating power for the intellectually and socially active personality. The researchers treat studies as a constructive activity in which students are able and ready to select the best-suited ways and methods of study. This kind of approach involves stages of the student active participation in the study processes as well as reflective processes; it guarantees student self-initiation, decision making and solutions to study-related problems, with the utmostly beneficial effect of attempts at inquiry, personal experience, creativity and personality maturity. In the works of Lithuanian researchers published in the period 1990–2015, the ideas are put forward that universities, as one of the major institution types where intellectual potential of personality gets developed and matured, have become the object of on-going transformations, and thus universities should be well-prepared to react immediately to the fast-changing social, economic, and cultural environment, they should search for new approaches in helping student to become critically thinking and creative personalities, with highly-developed adaptive skills that are so significant in the present-day world.